Evolutionary conservation in genes underlying human psychiatric disorders - Ogawa, Lisa M.; Vallender, Eric J. (Frontiers in Human Neuroscience, 2014)
Many psychiatric diseases observed in humans have tenuous or absent analogs in other species. Most notable among these are schizophrenia and autism. One hypothesis has posited that these diseases have arisen as a consequence of human brain evolution, for example, that the same processes that led to advances in cognition, language, and executive function also resulted in novel diseases in humans when dysfunctional. Here, the molecular evolution of genes associated with these and other psychiatric disorders are compared among species. Genes associated with psychiatric disorders are drawn from the literature and orthologous sequences are collected from eleven primate species (human, chimpanzee, bonobo, gorilla, orangutan, gibbon, macaque, baboon, marmoset, squirrel monkey, and galago) and thirty one non-primate mammalian species. Evolutionary parameters, including dN/dS, are calculated for each gene and compared between disease classes and among species, focusing on humans and primates compared to other mammals and on large-brained taxa (cetaceans, rhinoceros, walrus, bear, and elephant) compared to their small-brained sister species. Evidence of differential selection in primates supports the hypothesis that schizophrenia and autism are a cost of higher brain function. Through this work a better understanding of the molecular evolution of the human brain, the pathophysiology of disease, and the genetic basis of human psychiatric disease is gained.